PHYTOCHEMICAL STUDY, QUANTIFICATION OF TOTAL POLYPHENOLS AND EVALUATION OF THE ANTIOXIDANT CAPACITY OF THE BERRIES OF THE Jaltomata andagarae PLANT - Ascate Salinas, Santos (2024)
Tomatito is the common name given to the Jaltomata andagarae berry, located at more than 4000 meters above sea level, this plant is native to the Andagara hill, La Libertad region, Peru and like many high Andean plants, there are no studies regarding the nutraceutical properties of its fruit, but local residents consume the berries and comment, in addition to feeling a pleasant flavor when consuming them, an improvement in their mood and to give it scientific support, a phytochemical analysis was performed on the berries, finding different types of secondary metabolites. A quantification of total polyphenols using the Folin-Ciocalteu reagent which presented 412,1 ± 1,60 mg/Eq of gallic acid/100 grams of sample. The antioxidant capacity of the berries was also measured by the DPPH (1,1-diphenyl-2-picryl-hydrazyl) and ABTS (2,2'-azino-bis(3-ethylbenzothiazoline)-6-sulfonic acid) methods, finding a considerable trolox equivalent antioxidant capacity (TEAC) of 51,69 μmol ET/g sample and 107,6817 μmol ET/g sample, respectively. All these results indicate that the berry of this plant can be considered a nutraceutical food that would help preserve human health.